Evaluating Diaphragm Muscle Function in Children With Urinary Incontinence: Evaluating Diaphragm Muscle Function in Children With Urinary Incontinence - Gölgeli̇kay Sümeyra; Sertel, Meral; Kandur, Yaşar (Journal of Pediatric Nephrology, 2024)
Background and Aim: This study evaluates the respiratory muscle strength, quality of life (QoL), respiratory function of the diaphragm, participation in postural stabilization and functionality of active diaphragmatic breathing in postural stability in children with urine incontinence symptoms and lower urinary tract dysfunction and compares them with healthy children. Methods: This study included 49 healthy and 49 children with lower urinary tract dysfunction and urinary incontinence symptoms who applied to Kırıkkale University Pediatric Urology. Children’s QoL was evaluated using the pediatric urinary incontinence QoL scale. Their symptom severity was evaluated with the voiding disorders symptom score questionnaire, their respiratory muscle strength was evaluated with POWER breathe K5 and the diaphragm was evaluated with the dynamic neuromuscular stabilization method. Results: When comparing the diaphragm’s respiratory function, participation of the diaphragm in postural stabilization, and active breathing of the diaphragm in postural stabilization of the children, a significant difference was observed (P<0.05). Accordingly, asymptomatic children had greater inspiratory muscular strength, maximal inspiratory pressure and volume values than children with urinary system dysfunction. There was a difference in the pediatric urinary incontinence QoL scale and voiding disorders symptom score and it was due to the patient groups (P<0.05). Conclusion: Children with urinary incontinence symptoms and lower urinary tract dysfunction were found to have insufficient respiratory function, use of the diaphragm, and participation in postural stabilization of the diaphragm compared to asymptomatic children. Their respiratory muscle strength was lower.